Styrene biofiltration in a trickle-bed reactor - Novak,V. (2008)
The biological treatment of styrene waste gas in a trickle-bed filter (TBF) was investigated. The bioreactor consisted of a two-part glass cylinder (ID 150 mm) filled with 25 mm polypropylene Pall rings serving as packing material. The bed height was 1m. Although the laboratory temperature was maintained at 22 ºC, the water temperature in the trickle-bed filter was slightly lower (about 18 ºC).The main aim of our study was to observe the effect of empty-bed residence time (EBRT) on bioreactor performance at a constant pollutant concentration over an extended time period. The bioreactor was inoculated with a mixed microbial consortium isolated from a styrene-degrading biofilter that had been running for the previous two years. After three weeks of acclimation period, the bioreactor was loaded with styrene (100 mg.m-3). EBRT was in the range of 53 s to 13 s. A maximum elimination capacity (EC) of 11.3 gC.m-3.h-1 was reached at an organic loading (OL) rate of 18.6 gC.m-3.h-1.